PENERAPAN PP NO. 46 TAHUN 2013 PADA UMKM DI JAKARTA - wahyuni lestari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to explain that the application of PP No. 46 of 2013 to Small Medium Enterprise in Jakarta has been effective. This study uses primary data which obtained by distributing questionnaires and measured by using Likert Scale. The sample used in this study was Small Medium Enterprise in Jakarta especially West Jakarta, using convenience sampling method. The result of this study is the application of PP No. 46 of 2013 to Small Medium Enterprise in Jakarta with highly effective results are indicators of character deduction and/or collection, subject to VAT Tax, taxpayer obligations in the self assessment system, the depositing and reporting time. The indicators with effective results are tax subject, tax object and installment of WHT article 25. Meanwhile the indicators with less effective results are tariffs, compensation for losses and the timing of applying the PP No. 46 of 2013